The effectiveness of Instrumented Team Learning (ITL) and Team-Game-Tournament (TGT) as teaching strategies - Carvajal, Josefina C.; Lapa, Elisa G. (Iloilo City UP Visayas, 2004)
'This experimental study compared the effectiveness of Instrumented Team Learning (ITL) and Team-Game-Tournament (TGT) in the teaching of Biology and Chemistry. It utilized the Randomized Pre-Posttest Design and equated its research subjects employing Tuckman's Technique according to sex, age, science grade in previous year and IQ. This was conducted during the 1st semester, SY 2003-2004 at UP High School in Cebu. These were the findings: In Biology, ITL and TGT were effective teaching strategies as shown in their significant mean gain in achievement of the students from the pre-test to the post-test. However, after comparison of mean gains, the ITL was found to be a more effective strategy than TGT in teaching Biology. Likewise, the two strategies were effective in teaching Chemistry; but when the mean gains of the two groups were compared, it was revealed that TGT was a better strategy than ITL. Conclusions drawn were: ITL and TGT are effective strategies in Biology and Chemistry; and ITL is more effective than TGT in teaching Biology, while TGT is more effective than ITL in teaching Chemistry. One recommendations was for the teachers to include ITL, TGT and other cooperative learning designs in their repertoire of teaching strategies."
Keywords: University of the Philippines High School(UPHS) -- Cebu City; Teaching teams; Instrumented Team Learning (ITL).; Team-Game-Tournament (TGT).